2008
DOI: 10.1002/chem.200801407
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic Enantioselective Synthesis of N‐Substituted Aspartic Acids by Aspartate Ammonia Lyase

Abstract: The gene encoding aspartate ammonia lyase (aspB) from Bacillus sp. YM55‐1 has been cloned and overexpressed, and the recombinant enzyme containing a C‐terminal His6 tag has been purified to homogeneity and subjected to kinetic characterization. Kinetic studies have shown that the His6 tag does not affect AspB activity. The enzyme processes L‐aspartic acid, but not D‐aspartic acid, with a Km of ≈15 mM and a kcat of ≈40 s−1. By using this recombinant enzyme in the reverse reaction, a set of four N‐substituted as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 28 publications
1
48
0
1
Order By: Relevance
“…We anticipated that N -hydroxyaspartic acid ( N- hydroxy-Asp) would be the product of the FzmM reaction with L-Asp. Because of its reported instability, 20 we derivatised the enzymatic product with Fmoc-Cl followed by LC-MS analysis (Fig. S11–S14 † ), which showed that Fmoc- N- hydroxy-Asp was indeed produced (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…We anticipated that N -hydroxyaspartic acid ( N- hydroxy-Asp) would be the product of the FzmM reaction with L-Asp. Because of its reported instability, 20 we derivatised the enzymatic product with Fmoc-Cl followed by LC-MS analysis (Fig. S11–S14 † ), which showed that Fmoc- N- hydroxy-Asp was indeed produced (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, the use of biocatalysts is an attractive alternative option (Wohlgemuth 2010). Recently, the ammonia lyases and aminomutases (which exhibit ammonia lyase activity) have gained a lot of interest for the asymmetric synthesis of chiral α- and β-amino acids, with the advantage that they use readily available unsaturated acids as substrates (Turner 2010; Verkuijl et al 2010; Szymanski et al 2009; Wu et al 2009, 2010; Weiner et al 2008). However, most known ammonia lyases show low stability and therefore they are not compatible with the harsh reaction conditions that are usually required for industrial processes, such as high temperature, high pH, and high ammonia concentrations needed to catalyze the reverse reactions (Turner 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The Class II fumarases, encoded by the fumC gene, are thermostable homotetramers with no requirement for cofactors and catalyze the interconversion of fumarate to L -malate [2]. FumC proteins are widely distributed in nature, from prokaryotes like Bacillus subtilis , Pseudomonas aeruginosa , Sulfolobus solfataricus , and Saccharomyces cerevisiae , to mammals [3,8]. …”
Section: Introductionmentioning
confidence: 99%